2012
DOI: 10.2174/1874325001206010295
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Rupture and Osteoarthritis Progression

Abstract: Anterior Cruciate Ligament (ACL) rupture is a common sporting injury that frequently affects young, athletic patients. Apart from the functional problems of instability, patients with ACL deficient knees also develop osteoarthritis. Although this is frequently cited as an indication for ACL reconstruction, the relationship between ACL rupture, reconstruction and the instigation and progression of articular cartilage degenerative change is controversial.The purpose of this paper is to review the published liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 50 publications
0
22
0
1
Order By: Relevance
“…A well-established risk factor for OA is joint injury, the archetypal example being anterior cruciate ligament rupture of the knee, which substantially increases risk of knee osteoarthritis in the years following injury [89]. In the hip, a common form of joint injury is an acetabular labral tear, which warrants further study as a possible contributing factor to the development of hip OA.…”
Section: Etiology and Risk Factors For Hip Oamentioning
confidence: 99%
“…A well-established risk factor for OA is joint injury, the archetypal example being anterior cruciate ligament rupture of the knee, which substantially increases risk of knee osteoarthritis in the years following injury [89]. In the hip, a common form of joint injury is an acetabular labral tear, which warrants further study as a possible contributing factor to the development of hip OA.…”
Section: Etiology and Risk Factors For Hip Oamentioning
confidence: 99%
“…Acute anterior cruciate ligament (ACL) injury is a high-risk factor for the development of post-traumatic osteoarthritis 1-3 . Previous studies have shown that even with ACL reconstruction surgery, 50 to 70 percent of ACL-injured patients have radiological signs of osteoarthritis (OA) within 10-15 years post-injury 4, 5 .…”
Section: Introductionmentioning
confidence: 99%
“…This finding seems to be directly connected to the higher rate of dynamic instability, testified by the higher values observed with the pivot shift test in these patients. Statistical evaluation of the results highlighted the correlation between dynamic instability and arthritis progression, as previously described by Wong et al 42 and Ayeni et al 43 It is not clear why more instability was noted in the 1SHG group vs the 2SHG group, but it may be related to lower mechanical graft strength or less crosssectional area of the graft within the intercondylar notch, both of which are inherent to single-strand reconstruction.…”
Section: Andmentioning
confidence: 63%